(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم في هذا البحث دراسة معطيات المسح الاهتزازي المتوفرة لحوض الدو، وتم بنتيجتها تحديد بعض العواكس المأمولة نفطياً كعاكس الكوراشينا أنهدريت المغطي و الكوراشينا دولوميت الحامل. وضعنا لهما الخرائط الزمنية، وخرائط توزع السرع، ومن ثم وضعنا الخرائط العمقية وحددنا البنية الجيولوجية لهما للوقوف على المأمولية النفطية لهذين العاكسين. استناداً إلى هذه الدراسة وإلى الخرائط الموضوعة والمنفذة من قبلنا نؤكد على مأمولية العاكس كوراشينا دولوميت بسبب سماكته الملائمة، وتوفر الغطاء، والقاعدة، في حين أن العاكس كوراشينا أنهدريت يلعب دور الغطاء، على أن يصار إلى تدقيق هذه المعطيات بمسوح ثلاثية الأبعاد فوق البنى المحددة تتوج بعمليات حفر لاحقة. In this paper the available seismic data of AL-daw Depression were studied in order to define some petroleum potential reflections like Korushina Anhydrite (K.A) the cover, and Korushina Dolomite (K.D) the reservoir. Therefore the time and velocity maps for these two reflections were constructed. Finally, the depth maps, for both formations (K.A, K.D) were defined, in order to discuss the hydrocarbon potential. According to the obtained data, we emphasize the hydrocarbon potential of the K.D reflector, because of its suitable thickness, availability of cover, and base. On the other hand the K.A reflector plays an important role as reservoir cover. These results should be checked by a 3D surveys and then drilling operations.